(1)H, (13)C, and (15)N resonance assignment of photoactive yellow protein - Pool, Trijntje J. (Springer Netherlands, 2012)
Photoactive yellow protein (PYP) is involved in the negative phototactic response towards blue light of the bacterium Halorhodospira halophila. Here, we report nearly complete backbone and side chain (1)H, (13)C and (15)N resonance assignments at pH 5.8 and 20 °C of PYP in its electronic ground state.